LQG Control of Unmanned Aerial Vehicles Under Communication Constraints - Yan-Mei Wang; Qing-Quan Liu (Institute of Advanced Engineering and Science, 2013)
This paper addresses the LQG control problem for unmanned aerial vehicles (UAV) with time delays. In particular, the case with data-rate limitations is considered. It is shown in our results that the data rate of the communication channel has important effects on the control performances. It is derived that there exists a tradeoff between the data rate and the LQG cost. A quantization, coding, and control scheme is proposed to stabilize the unstable plant. Simulation results show the validity of the proposed scheme. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2426